Diagnosis and management challenges of acute mesenteric venous thrombosis in patients with liver cirrhosis: a single institution's experience - Zakaria, Hazem M.; Ammar, Khaled G.; Saleh, Sherif M.; Abbas, Mohammed; Gaballa, Nahla M.; Hammad, Essam M. (International Surgery Journal, 2017)
Background: Acute mesenteric venous thrombosis (MVT) is a dreadful complication of liver cirrhosis that requires prompt diagnosis and aggressive management for better outcome. The aim of this work was to study the diagnostic tools and the optimal management of acute MVT in patients with liver cirrhosis. Methods: It was a retrospective study including 40 patients with liver cirrhosis who were admitted to the surgical emergency and were eventually diagnosed as acute MVT between May 2011 to September 2016. The preoperative clinicopathological data, operative data and postoperative follow up were recorded. Results: Forty patients had acute MVT. Twenty five patients (62.5%) had prolonged prothrombin time, 18 patients (45%) had thrombocytopenia and 22 patients (55%) had low protein C. triphasic CT scan was the main diagnostic image in 28 patients, with sensitivity 100% and accuracy 96.9% in detection of intestinal infarction. Ten patients (25%) underwent conservative treatment with anticoagulant, while 30 patients (75%) were surgically explored and 28 patients of them had gangrenous bowel loops and underwent primary resection and anastomosis. Three patients underwent second look operation. Three patients had recurrent symptoms after 1 month of the first presentation. The overall 30- and 90-day mortality was 27.5% and 37.5% respectively. Conclusions: Cirrhotic patients may have hypercoagulable state and the usual laboratory tests don’t accurately assess the coagulation status in these patient. Acute MVT in cirrhotic patients has a high early morbidity and mortality that needs early diagnosis and urgent management with selective surgical intervention and proper anticoagulant.